Prioritizing fire management goals in a biodiversity hotspot - Heitor C. Sousa; Guarino R. Colli; Adriana Malvasio (Perspectives in Ecology and Conservation)
Understanding the priorities and motivations of key actors is essential to setting fire management goals toward sustainability and resilience in a changing world. To investigate how key actors in fire management, rural residents and environmental specialists, prioritize fire management goals and assess their attitudes regarding fire use, fire regime effects, and Integrated Fire Management (IFM) in the Brazilian Cerrado savannas, we used an Analytic Hierarchy Process framework and Bayesian multilevel models. We identified minor differences in prioritizing fire management goals between rural interviewees and environmental specialists. Both groups independently regarded (1) pest control and farming as the lowest priorities and (2) protecting water resources and biodiversity conservation as the most important compared to other fire management goals. Despite the similarities, participants with higher education prioritized conserving biodiversity and its traditional use while emphasizing the importance of controlled fire use. Most specialists approved the use of IFM in protected areas (91.84%) and private areas (79.59%). Specialists also suggested improvements to IFM regarding mobilization and education, laws and regulations, surveillance, fund-raising, and scientific research. Our findings show that we should expect minor tradeoffs between key actors and their fire management goals, revealing a fruitful path for implementing a large-scale IFM in Cerrado that is aligned with the needs of local communities and avoiding conflicts.